Effects of hot-deformation on grain boundary precipitation and segregation in Ti-Mo microalloyed steels. (5th March 2018) - Wang, Jiangting; Hodgson, Peter D.; Bikmukhametov, Ilias; Miller, Michael K.; Timokhina, Ilana
Abstract: Hot-deformation can refine grain size and change the dynamics of austenite-ferrite phase transformation during thermo-mechanical processing of microalloyed steels. Here, atom probe tomography has been used to characterize nanoscale precipitates and segregation in Ti-Mo microalloyed steels processed with and without hot-deformation at 890 °C. It provides a comprehensive understanding of solute redistribution in both the grain interior and grain boundary regions. The results show that coarse (Ti, Mo)C precipitates are formed at grain boundaries, whereas fine precipitates are densely distributed in grain interiors, regardless of deformation conditions. Precipitate-free zones are developed near grain boundaries in the undeformed Ti-Mo steel, but absent in the hot-deformed steel. The elimination of precipitate-free zone in the hot-deformed steel is attributed to the high dislocation density and accelerated γ  →  α transformation caused by hot-deformation. The majority of Ti, Mo, and C atoms partition into (Ti, Mo)C precipitates, but Mn, Si, and Al atoms are mainly in solute state in ferrite matrix and segregation at grain boundaries. The hot-deformation significantly changes the C segregation at grain boundaries, but has little effect on other solute elements. Graphical abstract: Image 1 Highlights: Coarse (Ti, Mo)C precipitates are observed at grain boundaries for both hot-deformed and undeformed Ti-Mo microalloyed steels. Precipitate-free zones are observed near grain boundaries only in the undeformed Ti-Mo microalloyed steel. The accelerated austenite-to-ferrite phase transformation as a result of hot-deformation leads to the absence of precipitate-free zone. Hot-deformation promotes the formation of coarse (Ti, Mo)C precipitates at grain boundaries, but reduces plane segregation of C.